Proceedings of the 1st International Workshop on Games and Software Engineering 2011
DOI: 10.1145/1984674.1984677
|View full text |Cite
|
Sign up to set email alerts
|

Modding as a basis for developing game systems

Abstract: This paper seeks to briefly examine what is known so far about game mods and modding practices. Game modding has become a leading method for developing games by customizing extensions to game software. The research method in this study is observational and qualitative, so as to highlight current practices and issues that can be associated with software engineering foundations. Numerous examples of different game mods and modding practices are identified throughout.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 14 publications
0
6
0
2
Order By: Relevance
“…Our activity can be characterized as a project-based learning activity and emphasizes in the challenging balance between production and process [1]. Related studies [6] [7] have proved the value of game prototyping in SE. While these studies address the issue of creative development of computer games, they do not explicitly explore how these activities are experienced by participants and can be potentially improved.…”
Section: Related Workmentioning
confidence: 96%
See 1 more Smart Citation
“…Our activity can be characterized as a project-based learning activity and emphasizes in the challenging balance between production and process [1]. Related studies [6] [7] have proved the value of game prototyping in SE. While these studies address the issue of creative development of computer games, they do not explicitly explore how these activities are experienced by participants and can be potentially improved.…”
Section: Related Workmentioning
confidence: 96%
“…Modding, the practice and process of developing game mods, is typically a "Do It Yourself" (DIY) approach to game development [6] by reusing game software. For this purpose, well known and validated Software Engineering (SE) theories and techniques for development and innovation can be applied to game development.…”
Section: Introductionmentioning
confidence: 99%
“…They found that untagged mods are the least popular. Scacchi [51][52][53] gives an overview of the types of mods and the modding community, and describes modding as an open source approach to extending closed source software. We are the first to conduct a large-scale study of the release schedule and bug reports of game mods.…”
Section: Related Workmentioning
confidence: 99%
“…According to Scacchi (2011), modding is a way to learn to work with others as a person who creates a mod trains to work in a team and to manage a group project. During the experiments of El-Nasr and Smith (2006), the students first learnt to divide the tasks among groups of two and share their skills.…”
Section: Collaborating To Learn and Learning To Collaboratementioning
confidence: 99%